Adenosine A1, A2a, A2b, and A3 receptors in hematopoiesis. 2. Expression of receptor mRNA in resting and lipopolysaccharide-activated mouse RAW 264.7 macrophages - Štreitová, Denisa; Hofer, Michal; Holá, Jiřina; Vacek, Antonín; Pospíšil, Milan (Physiological research, 2010)
Expression of mRNA for adenosine receptor subtypes A(1), A(2a), A(2b), and A(3) in normal and lipopolysaccharide (LPS)-activated murine RAW 264.7 macrophages has been investigated using the method of quantitative real-time polymerase chain reaction. The results have shown a very low, unquantifiable expression of adenosine A(1) receptor mRNA in both normal and LPS-activated macrophages. The other three adenosine receptor mRNAs have been found to be expressed at various but always quantifiable levels. Activation of the macrophages by LPS induced upregulation of the expression of adenosine receptor A(2a) and A(2b) mRNA, whereas the expression of adenosine receptor A(3) mRNA was downregulated. Unstimulated macrophages exhibited a high expression of the A(2b) adenosine receptor mRNA. The findings are discussed from the point of view of the antiinflammatory and hematopoiesis-stimulating roles of the adenosine receptor signaling.
Keywords: Polymerase Chain Reaction; Macrophages; receptor adenosinový A2A; messenger RNA; makrofágy; zvířata; Time Factors; Receptors, Purinergic P1; polymerázová řetězová reakce; Animals; časové faktory; Receptor, Adenosine A2A; receptor adenosinový A1; Receptor, Adenosine A2B; Lipopolysaccharides; RNA, Messenger; Mice; financování organizované; aktivace makrofágů; Cell Line; Hematopoiesis; Receptor, Adenosine A3; receptor adenosinový A3; Macrophage Activation; hematopoéza; Receptor, Adenosine A1; lipopolysacharidy; buněčné linie; myši; receptor adenosinový A2B; Financing, Organized; regulace genové exprese; Gene Expression Regulation; purinergní receptory P1